Применение атомарных функций для синтеза деконволюционных окон с целью реставрации изображений - Афанасьев, В. А. (ХНУРЭ, 2008)
A new class of finite deconvolution windows for image restoration is considered. The windows are defined as linear combinations of atomic function shift products. The linear combination coefficients are chosen so as to minimize some functional
Keywords: атомарная функция; синтез деконволюционных окон